The Optimization Management of Special Autonomy Funds for Acehnese People Welfare - Hasan, Effendi; Dahlawi; Ubaidullah; Novita Sari; Nofriadi; Helmi (International Journal of Criminology and Sociology, 2022)
This research aimed to examine the factors contributing to the less optimum management of the Aceh special autonomy funds for the development and welfare of the Acehnese people. Specifically, Aceh received the special autonomy funds of IDR 56.67 trillion from 2008 to 2018, yet the vast funds have not been successful in change the face of Aceh in terms of poverty, unemployment, and other social diseases. This study employed a descriptive qualitative research design and data collection involved interviews, observation, and document study. The informants were selected by purposive and snowball sampling. The results of the study showed that three factors contributed to the less optimum management of the Aceh special autonomy funds. First, the regulation of the Aceh special autonomy funds management has not been standardized and frequently changed, and thus it cannot be used as a complete guideline. Second, the management authority of the special autonomy funds was unclear between the provincial and the district/city government, resulting in no good coordination between the parties. Third, the poor management of the Aceh special autonomy funds led to the poorly targeted development and community empowerment. Based on the findings, it can be concluded that these three factors hindered the Aceh special autonomy funds from fulfilling the goals of realizing the development and welfare for the Acehnese people.